Effect of Appliance Slipping and Deep Breathing to Decreasing Pain Scale in Patients - Armita S; Rahmat Hidayat; Safruddin Safruddin; Muhammad Hisyam (An Idea Nursing Journal, 2025)
Fracture is one of the emergency cases in orthopedics which requires fast and precise management to avoid morbidity and mortality caused. Fracture management includes surgery to clean the crushed bones, perform internal and external fixation and connect the broken bones with special pins, plates, screws, or rods. After surgery, pain due to surgical incisions can be reduced. Method: This type of research is descriptive by establishing a case study method that can explore the problem of Nursing Care in patients with fractures. The results of this study indicate there was a decrease in the pain scale in fracture patients after splinting and deep breathing relaxation; this was shown by the pain scale in patients after the splint dressing and deep breathing relaxation was in the range of 3-7, and before the splint dressing and deep breathing relaxation was carried out it was in the range 6-9. This happens because applying a splint can reduce the movement of the bone or injured area so that it does not cause a painful sensation in the patient. So splint application and deep breathing relaxation have an effect on reducing the pain scale in fracture patients after being given pain management measures with splint application and deep breathing relaxation. Conclusion:Based on the results of the discussion of the results of the Implementation of nursing carried out on Mr. H with pain management, it can be concluded that there is an effect of splint installation and deep breathing relaxation. In the assessment at 12.30, the results obtained before deep breathing relaxation were obtained: the patient complained of pain with a pain scale of 8 (severe), respiratory rate of 24x /, pulse rate of 118x /, and after the splint installation and deep breathing relaxation were carried out, the patient said the pain was moderate with a pain scale of 6.Suggestion: It is expected that the family and patient handle problems experienced by patients by teaching deep breathing relaxation if pain occurs.